PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DALAM DIET RENDAH PURIN PADA LANSIA DENGAN ARTRITIS GOUT DI WILAYAH KERJA PUSKESMAS KEMBANG TANJONG KABUPATEN PIDIE - Srimawati Srimawati; Neila Fauzia; Risna Risna (Jurnal Sains Riset, 2022)
Gouty arthritis is the third most common type of arthritis after osteoarthritis and rheumatism outside the joints, this disease interferes with the quality of life of the sufferer. Health education is needed to increase the knowledge of the elderly with gout in dieting and living principles that are accustomed to consuming low-purine foods. The purpose of the study was to determine the effect of health education on knowledge of a low-purine diet in the elderly with gouty arthritis in the working area of the Kembang Tanjong Public Health Center, Pidie Regency in 2022. This study was a quasi-experimental study (one group pretest posttest design). The population is the elderly who suffer from gouty arthritis as many as 120 people. Sampling using total sampling technique. The results of the study of knowledge in a low-purine diet in the elderly with gouty arthritis before being given health education were still lacking, namely 54.2% and after being given health education the majority had good knowledge, namely 45%. The results of the Paired Sample t-test obtained a significance of 0.000 = 0.05, so there is an effect of health education on knowledge in low-purine diets in the elderly with gouty arthritis. Suggestions for the elderly should be more obedient in a low-purine diet to prevent a decrease in uric acid levels in the body.Keyword : Health Education, Knowledge, low-purine diets, Gouty arthritis